FAKTOR-FAKTOR YANG MEMENGARUHI MINAT KUNJUNGAN KE OBJEK HATUSUA BEACH DI DESA HATUSUA, KABUPATEN SERAM BAGIAN BARAT - Selfanay, Destalia; Latupapua, Yosevita; Seipalla, Billy (PT. BARRINGTONIA ASIATICA LESTARI, 2024)
The aim of this research is to find out what factors influence interest in visiting the Hatusua Beach Object and also which factors (attraction, accessibility, services, infrastructure and entrance tickets) are the most dominant in influencing interest in visiting the Hatusua Beach Object. This research used a qualitative descriptive analysis method where the data was collected and then analyzed by summarizing various conditions and situations in the form of interview results and observations regarding the problems studied in this field and can provide an overview of the characteristics of visitors to the Hatusua Beach tourist attraction. The results of this research are that the factors that influence interest in visiting the Hatusua Beach object are attractiveness with a percentage of 36%, accessibility with a percentage of 10%, service, infrastructure with a percentage of 15%, and entrance tickets with a percentage of 28%. The factors (attractiveness, accessibility, service, infrastructure and entrance tickets) that are most dominant in influencing interest in visiting the Hatusua Beach object are attractiveness with a percentage of 36%.